2014
DOI: 10.5264/eiyogakuzashi.72.113
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Family Dinner Frequency and Voluntary Mealtime Communication with Dietary Attitudes, Dietary Behaviors, and Quality of Life: A Cross-sectional and Longitudinal Study of 5th and 8th Grade Students

Abstract: QOL 核家族 461(77. 2) 233(77. 2) 228(77. 3) 拡大家族 135(22. 6) 69(22. 8) 66(22. 4) その他 1( 0. 2) 0( 0. 0) 1( 0. 1( 3. 6) 2( 6. 7) 1( 0. 9) 4( 4. 3) 3( 7. 9) 11(20. 4) まったくあてはまらない 3( 2. 4) 1( 0. 9) 3(10. 7) 1( 3. 3) 1( 0. 9) 3( 3. 2) 1( 2. 6) 3( 5. 6) 家族と一緒に食事をすることは重要である(共食の重要性) とてもあてはまる 57(45. 2) 46(41. 4) 8(28. 6) 12(40. 0) 0. 35 64(58. 7) 34(36. 2) 14(36. 8) 11(20. 4) <0. 001 まあまああてはまる 46(36. 5) 42(37. 8) 12(42. 9) 10(33. 3) 36(33. 0) 36(38. 3) 15(39. 5) 23(42. 6) (A&B,C,D) どちらともい… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Despite participants with higher household incomes showing lower frequency of family meals, these participants conversed more about food during mealtimes. A previous study showed that Japanese children who engaged in mealtime conversations during meals had better dietary attitudes, eating behaviors, and quality of life; good health status; higher vegetable intake; and good table manners [ 29 , 30 , 46 ]. The results of our study help to highlight the importance of positive conversation at the dining table, which may be influenced by working parents being unable to be at home for mealtimes.…”
Section: Discussionmentioning
confidence: 99%
“…Despite participants with higher household incomes showing lower frequency of family meals, these participants conversed more about food during mealtimes. A previous study showed that Japanese children who engaged in mealtime conversations during meals had better dietary attitudes, eating behaviors, and quality of life; good health status; higher vegetable intake; and good table manners [ 29 , 30 , 46 ]. The results of our study help to highlight the importance of positive conversation at the dining table, which may be influenced by working parents being unable to be at home for mealtimes.…”
Section: Discussionmentioning
confidence: 99%
“…These studies argue that if children eat with their families, they will eat more fruits and vegetables. Similar evidence is also found with Japanese cases, as children eating with family members are more likely to eat more nutritionally balanced diets than those who eat alone [1,16,17], and are likely to have higher recognition of healthy eating [18]. However, these studies focus on the effects of nutrition education on children, rather than the longer-term effects of nutrition education during childhood on adults, and some studies provide mixed results on the relationship [19].…”
Section: Introductionmentioning
confidence: 55%
“…The health and development of children are influenced by conversations with parents during meal preparation [26, 27] and the child feeding practices of the parents [28], which may alleviate some parental concerns. In our study, the concerns of children were expressed from the perspective of the parents.…”
Section: Discussionmentioning
confidence: 99%